2008
DOI: 10.1124/jpet.108.145326
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II-Induced Hypertension Is Associated with a Selective Inhibition of Endothelium-Derived Hyperpolarizing Factor-Mediated Responses in the Rat Mesenteric Artery

Abstract: Hypertension has been shown to be associated with impaired endothelium-derived hyperpolarizing factor (EDHF)-mediated arterial relaxation and hyperpolarization. Treatments of hypertensive rats with inhibitors of the renin-angiotensin system have been shown to restore both EDHF-mediated responses and the expression of connexins involved in the intercellular transfer of the hyperpolarization in mesenteric arteries. The present study was designed to determine whether chronic treatment of rats with angiotensin II … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 38 publications
1
51
0
Order By: Relevance
“…Previous studies in large, elastic, superior mesenteric arteries of SHRs also described decreases in endothelial Cxs and associated these changes with diminished EDHF responses, both reversed by candesartan treatment (Kansui et al, 2004). A causal link between EDHF and endothelial Cx expression in these arteries was also made after chronic treatment with angiotensin II (Dal-Ros et al, 2009). In contrast, we found no association between reduced endothelial Cxs40 and 43 and EDHF relaxation in the downstream muscular branches of the superior mesenteric artery.…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies in large, elastic, superior mesenteric arteries of SHRs also described decreases in endothelial Cxs and associated these changes with diminished EDHF responses, both reversed by candesartan treatment (Kansui et al, 2004). A causal link between EDHF and endothelial Cx expression in these arteries was also made after chronic treatment with angiotensin II (Dal-Ros et al, 2009). In contrast, we found no association between reduced endothelial Cxs40 and 43 and EDHF relaxation in the downstream muscular branches of the superior mesenteric artery.…”
Section: Discussionmentioning
confidence: 91%
“…The finding that these responses could be restored by an ACEI, by an ARB, or by a combination of the two has been taken as an indication of the negative influence of the RAS on EDHF-mediated responses (54,55). Indeed, in a very recent study, Dal-Ros et al (56) demonstrated in the rat that Ang II-induced hypertension is associated with selective impairments of EDHF-mediated relaxation and hyperpolarization in the mesenteric artery. In the present study, two-week treatment with losartan improved the EDHF-mediated relaxation in mesenteric arteries from GK rats even though the treatment was begun when the rats were already in the established phase of type 2 diabetes (i.e., at 32 -36-week-old).…”
Section: Discussionmentioning
confidence: 96%
“…Both in AngII [6] and in other hypertensive models [2,40], AHT is associated with depolarized membrane potentials of the VSMC. This depolarization may be due to attenuated basal NO release and (partial) removal of the hyperpolarizing effect of NO [2].…”
Section: Discussionmentioning
confidence: 98%
“…Because this might result in a reduction of the hyperpolarizing effect of NO on the VSMCs [2,6], this would shift the window current induced contraction curves to lower K + concentrations without affecting the functional properties of the L-type Ca 2+ channels [8]. In order to exclude that the shift of the window current induced contraction curves in aortic segments of mice with AngII-induced AHT was due to attenuated NO availability and the subsequent depolarization of VSMCs, aortic segments from saline-and AngIItreated mice were studied before and after inhibition of basal NO release with 300 μM L-NAME (Fig.…”
Section: Angii-induced Aht Shifts the Aortic Window Current Induced Cmentioning
confidence: 99%